EXPERIMENTAL AND NUMERICAL RESEARCH ON FLOW IN THE LAST STAGE OF 1090MW STEAM TURBINE - Michal Hoznedl; Kamil Sedlák (Acta Polytechnica CTU Proceedings)
The paper deals with experimental and numerical research in the last stage of real 1090MW steam turbine with the last steel blade length 1220mm placed in nuclear power station. The last stage was equipped with twelve static pressure taps. It was also possible to probe in two planes - before and behind the last stage using pneumatic or optical probes. A number of last stage flow parameters were determined at the root and tip wall for nominal turbine output. Among those parameters are static pressures, Mach and Reynolds numbers, last stage reactions and steam wetness. All the directly measured and evaluated flow parameters are taken from locally measured points and that is why even 3D CFD calculation of the whole system - last stage, diffuser and exhaust hood was implemented. Measured and calculated parameters are compared. Especially static pressures are in very good agreement; the only steam wetness has bigger difference due to different measurement position. Locally measured values are enough to estimate the flow behavior of the last stage. On the other hand, the CFD simulations with well determined boundary conditions, meshes and geometry and is effective tool to simulate even very complicated flow structures in the last stage and exhaust hood.